2021
DOI: 10.3389/fmicb.2021.698944
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Characterization of Fitness and Convalescent Antibody Neutralization of SARS-CoV-2 Cluster 5 Variant Emerging in Mink at Danish Farms

Abstract: In addition to humans, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can transmit to animals that include hamsters, cats, dogs, mink, ferrets, tigers, lions, cynomolgus macaques, rhesus macaques, and treeshrew. Among these, mink are particularly susceptible. Indeed, 10 countries in Europe and North America reported SARS-CoV-2 infection among mink on fur farms. In Denmark, SARS-CoV-2 spread rapidly among mink farms and spilled-over back into humans, acquiring mutations/deletions with unknown cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…However, Y453F in particular, negatively impacts replication kinetics of SARS-CoV-2 in human cells, potentially explaining why the Danish mink-origin outbreaks did not propagate further following the culling of the mink. Furthermore, in line with other studies 16,17,31 , we found none of these mutations had a large antigenic impact, so vaccination is likely to remain effective against mustelid-adapted strains. Finally, we have shown that several VOC strains, or VOC-associated mutations, partially adapt SARS-CoV-2 spike to mustelid ACE2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, Y453F in particular, negatively impacts replication kinetics of SARS-CoV-2 in human cells, potentially explaining why the Danish mink-origin outbreaks did not propagate further following the culling of the mink. Furthermore, in line with other studies 16,17,31 , we found none of these mutations had a large antigenic impact, so vaccination is likely to remain effective against mustelid-adapted strains. Finally, we have shown that several VOC strains, or VOC-associated mutations, partially adapt SARS-CoV-2 spike to mustelid ACE2.…”
Section: Discussionsupporting
confidence: 91%
“…The D614G containing strain, SARS-CoV-2/England/IC19/2020, was used as previously described 41 . The Cluster 5 isolate -SARS-CoV-2/hu/DK/CL-5/1was isolated as previously described 16 and was kindly provided by Kevin Bewley at Public Health England. All viral stocks used in this study were grown in Vero cells in OptiPRO SFM containing 2x GlutaMAX.…”
Section: Viruses Reverse Genetics and Growth Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, phylogenetic evidence indicated that zoonotic mink-to-human transmission of SARS-CoV-2 occurred at both Dutch and Danish farms [ 94 , 95 , 96 , 98 , 182 , 183 ]. It was determined that between June and November 2020, 214 human cases of COVID-19 were identified in Denmark with SARS-CoV-2 variants associated with farmed mink [ 98 , 181 ].…”
Section: Main Textmentioning
confidence: 99%
“…The D614G containing strain, SARS-CoV-2/England/IC19/2020, was used as previously described 41 . The Cluster 5 isolate -SARS-CoV-2/hu/DK/CL-5/1 -was isolated as previously described 16 and was kindly provided by Kevin Bewley at Public Health England. All viral stocks used in this study were grown in Vero cells in OptiPRO SFM containing 2x GlutaMAX.…”
Section: Viruses Reverse Genetics and Growth Kineticsmentioning
confidence: 99%